2015
DOI: 10.1177/1528083714567239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glass and polypropylene fibers in cementitious composites containing waste stone powder

Abstract: In this study, stone powder as a waste material was used to fabricate cementitious composite samples. Neat (non-modified) cementitious samples were composed of gravel, cement, sand, water, and waste stone powder. Flexural and compressive strength tests showed that flexural and compressive strength could be improved by increasing waste stone powder weight percentage. In addition, the experimental results illustrated that samples containing waste stone powder present more flexural and compressive strength in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The extruded panels satisfied all performance requirements related to fire resistance. Abdellahi and Hejazi [22] used WSP to fabricate cementitious composite panels reinforced with glass and polypropylene (PP) fibers. Experimental results showed that the use of WSP increases both flexural and compressive strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extruded panels satisfied all performance requirements related to fire resistance. Abdellahi and Hejazi [22] used WSP to fabricate cementitious composite panels reinforced with glass and polypropylene (PP) fibers. Experimental results showed that the use of WSP increases both flexural and compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that the use of WSP increases both flexural and compressive strength. This is due to the fact that WSP plays as filler role in the composite mixture [22].…”
Section: Introductionmentioning
confidence: 99%
“…25 Hence, some studies have been carried out to investigate the effect of WSP on the mechanical properties of civil products. 2628 The results showed that using WSP improves the mechanical and thermomechanical properties of samples.…”
Section: Introductionmentioning
confidence: 96%
“…Concrete is one of the cement products used in many parts of construction, such as buildings, bridges, tunnels, and roads. Studies show that the cement industry demands a vast amount of energy and also releases a large amount of carbon dioxide into the atmosphere-up to 13,500 tons per year, which is 7% of greenhouse gas emissions annually produced and causes additional environmental pollution [1,2]. erefore, many scholars are currently devoted to the study of cement alternative materials.…”
Section: Introductionmentioning
confidence: 99%